2014
DOI: 10.3389/fpls.2014.00004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of water, salinity, and cold stress responses by salicylic acid

Abstract: Salicylic acid (SA) is a naturally occurring phenolic compound. SA plays an important role in the regulation of plant growth, development, ripening, and defense responses. The role of SA in the plant–pathogen relationship has been extensively investigated. In addition to defense responses, SA plays an important role in the response to abiotic stresses, including drought, low temperature, and salinity stresses. It has been suggested that SA has great agronomic potential to improve the stress tolerance of agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
425
3
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(453 citation statements)
references
References 177 publications
(221 reference statements)
13
425
3
12
Order By: Relevance
“…Application of SA has been shown to influence plant growth by promoting protective reactions involving photosynthetic pigments and membrane integrity. 26,27 Of the strategies capable of counteracting salt stress and its detoxification, the pivotal role of AsA-GSH pools and the coordination between AsA-GSH regenerating enzymes with other enzymatic antioxidants should be studied. Activities of enzymes in the ascorbate glutathione cycle are increased under salt stress suggesting a requirement for increased activity of the cycle under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Application of SA has been shown to influence plant growth by promoting protective reactions involving photosynthetic pigments and membrane integrity. 26,27 Of the strategies capable of counteracting salt stress and its detoxification, the pivotal role of AsA-GSH pools and the coordination between AsA-GSH regenerating enzymes with other enzymatic antioxidants should be studied. Activities of enzymes in the ascorbate glutathione cycle are increased under salt stress suggesting a requirement for increased activity of the cycle under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cold acclimation in plants is a potent inducer of salicylic acid and ethylene accumulation [47][48][49][50], transcription factors [40], calcium signaling [51,52], pathogenesis-related and antifungal proteins [5] along with anatomical changes, and cell membrane or cytoskeleton restructuring [53]. Consequently, besides plant antioxidative systems several other host factors should be considered as potential mechanisms behind the observed resistance response in cold hardened barley challenged by infection with P. teres f. teres.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that SA also plays an important Chapter 1 36 role in abiotic stress-induced signaling and tolerance [11,18]. Particularly, it has been proposed that SA may induce thermotolerance in several plant species [19][20][21][22] …”
Section: Resultsmentioning
confidence: 99%
“…Plant responses to external stimuli are mainly mediated by phytohormones, whose involvement in abiotic stress responses has been deeply studied [9][10][11][12]. Under drought or high salinity, abscisic acid (ABA) seems to be an important stress-signaling hormone [13,14], involved in the regulation of stomatal closure, synthesis of compatible osmolytes and up-regulation of genes leading to adaptive responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation